2015
DOI: 10.1538/expanim.15-0028
|View full text |Cite
|
Sign up to set email alerts
|

The relation between the effect of a subhypnotic dose of thiopental on claw pain threshold in rats and adrenalin, noradrenalin and dopamine levels

Abstract: Thiopental sodium (TPS) needs to be applied together with adrenalin in order to establish its analgesic effect in general anesthesia. We aimed to investigate the effect of TPS on the claw pain threshold in rats and evaluated its relationship with endogenous adrenalin (ADR), noradrenalin (NDR), and dopamine (DOP) levels. Intact and adrenalectomized rats were used in the experiment. Intact animals were divided into the following groups: 15 mg/kg TPS (TS), 0.3 mg/kg ADR+15 mg/kg TPS (ATS) and 0.3 mg/kg ADR alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…For this reason, chemotherapy-induced PNP models have gained importance when they are directed toward the prevention of the side effects of cancer drugs. In recent years, the paw withdrawal test has been widely used as a method of pain evaluation [ 2 , 20 ]. In particular, the reason for choosing the paw withdrawal test to assess chemotherapy-induced PNP is that neuropathic pain first appears in this region [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, chemotherapy-induced PNP models have gained importance when they are directed toward the prevention of the side effects of cancer drugs. In recent years, the paw withdrawal test has been widely used as a method of pain evaluation [ 2 , 20 ]. In particular, the reason for choosing the paw withdrawal test to assess chemotherapy-induced PNP is that neuropathic pain first appears in this region [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increases in MDA were reported in the cisplatin-induced peripheral neurotoxicity model, whereas tGSH levels were decreased [ 33 ]. Recent studies have also suggested a significant link between pain/analgesia and oxidant/antioxidant parameters [ 2 , 9 ]. In the present study, increased amounts of IL-1 β and MDA and a decreased amount of tGSH were observed in the blood serum of the rats given cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Thiopental administered at subanesthetic and anesthetic doses leads to oxidative stress in the brain striatum, likely because of the suppressed production of adrenaline, which causes systemic hypotension and associated high-risk complications [ 18 ]. Published studies have shown that, unlike ketamine, thiopental suppresses release of catecholamines [ 36 ] and decreases the amount of adrenaline in rats even at subanesthetic doses [ 16 ]. Furthermore, it was reported that hyperalgesia occurred in the animals receiving thiopental alone, while analgesia was observed in the animals receiving thiopental combined with adrenaline.…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies were found in the literature demonstrating that thiopental induces oxidative stress in heart tissue. Unlike ketamine, thiopental decreases the release of adrenaline, blood pressure, and cardiac pulse power [ 16 , 17 ]. These negative effects (hypotension) increase the risk for myocardial infarction [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation